Minecraft. Master builds : a showcase of breathtaking creations - Stone, Tom (Minecraft., 2022)
"Packed with stunning illustrations, Minecraft: Master Builds showcases the creations that have taken the game to new levels, and introduces the builders behind them. Explore all the possibilities of Minecraft, from stunning underwater sculptures to impressive space panoramas, or travel through time to visit grand medieval towns and futuristic cityscapes. Each colossal creation is shown in beautifully rendered illustrations to highlight the painstaking details that make these builds masterful. The exclusive interviews with the builders shed light on the creative forces and processes behind each build. Whether you're marveling at the wonders that Minecraft's greatest builders have to offer, or searching for inspiration to become one yourself, your tour begins here."--